LINKING INFLATION, INTEREST RATES, AND BOOK VALUE TO SHARE PRICES: AN EMPIRICAL STUDY OF LQ45 INDEX COMPANIES ON THE INDONESIA STOCK EXCHANGE - Ni Komang Sinta Dewi; I Wayan Widnyana; I Wayan Sukadana (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2025)
The stock prices of LQ45 Index companies fluctuated during the 2020-2023 period. The lowest decline in LQ45 Index stock prices in 2020 was 624 per share, caused by the impact of Covid-19, and the highest increase in LQ45 Index stock prices in 2022 was 1,085 per share. Meanwhile, at the beginning of 2023, the movement of LQ45 index stock prices weakened, driven by a decline in stocks. The purpose of this study is to identify the impact of inflation, interest rates, and book value on the stock prices of LQ45 Index companies listed on the Indonesia Stock Exchange. The objects of this study are inflation, interest rates, book value, and stock prices of LQ45 Index companies listed on the Indonesia Stock Exchange. The sample in this study consisted of 29 LQ45 Index companies. The data collection method used the non-participant observation technique. The data analysis techniques used were classical assumption tests, multiple linear regression analysis, multiple correlation analysis, determination analysis, and t-tests. The conclusion of this study reveals that inflation and interest rates do not affect the stock prices of LQ45 Index companies listed on the Indonesia Stock Exchange in the 2021-2023 period. Meanwhile, book value has a positive and significant effect on the stock prices of LQ45 Index companies listed on the Indonesia Stock Exchange in 2021-2023.